Who profits from trade facilitation initiatives? - Bernard Hoekman; Ben Shepherd (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2013)
Extensive research has demonstrated the existence of large potential welfare gains from trade facilitation - measures to reduce the overall costs of the international movement of goods. From an equity perspective an important question is how those benefits are distributed across and within nations. After discussing the possible impacts of trade facilitation, we use firm-level data for a wide variety of developing countries to investigate whether it is mostly large firms that benefit from trade facilitation. We find that firms of all sizes export more in response to improved trade facilitation. Our results suggest that trade facilitation can be beneficial in a range of countries, including those that are primarily involved in value chains as suppliers.
Keywords: F13; F14; O24; 330; Trade facilitation; trade costs; WTO; firm-level data; developing countries; global value chains; supply chains